(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص : العلاجات النفسية في تطور مستمر متخذة منحى الموجات، موجة أولى فثانية فثالثة...، ويعتبر تعقد، عمق وتركيب الأمراض النفسية من أحد الأسباب الرئيسية لهذا التطور، فأصبح الاهتمام بالمريض وليس بالمرض، ومن بين الأمراض الخطيرة التي تهدد وجود الإنسان السرطان، وتعد أبعاده النفسية التي تتمحور رئيسيا، في اضطرابات القلق، الاكتئاب والصدمة، من أخطر الاضطرابات النفسية وأعقدها على الإطلاق وليست هي نفسها المتناولة في الحالات العادية، ما أدى إلى تغيير النظرة التقليدية لعلم النفس، فأصبح يتناولها علم نفس الأورام بدلا عن البسيكوسوماتيك، وأضحى تكامل العلاجات النفسية في موجتها الثالثة أكثر من ضرورة، ويعتبر العلاج النفسي بخفض الحساسية بحركات العين وإعادة المعالجة المدمج ببروتوكولات علم النفس الايجابي وعلى رأسها بروتوكول التفاؤل وتطوير وتثبيت الموارد المقترح من طرف الباحثين تكفلا نفسيا متكاملا شاملا تكشفت نتائجه الجيدة حديثا. كلمات دالة : علاج نفسي، حركات العينين، علم النفس الايجابي، تفاؤل، تطوير وتثبيت الموارد، علم النفس الأورام، سرطان. Abstract: Psychotherapy are in continuous development, taking the direction of waves, first wave, second wave, third ..., and the complexity, depth and composition of the psychological disease one of the main reasons for this development, so concern for the patient and not disease, and among the serious diseases that threaten the existence of man is cancer, and its psychological dimensions are which centered mainly on anxiety disorders, depression and trauma, is one of the most dangerous and complex disease disorders at all, and it is not the same as the one used in normal cases, which led to a change in the traditional view of psychology, so that it became covered by psycho-oncology instead of psychosomatic, and the integration of psychotherapy became in its wave the third is more than a necessity, and psychotherapy is considered by reducing sensitivity to Eye Movement Desensitization and Reprocessing Psychotherapy with positive psychology protocols, on top of which is the protocol for optimism and the development and installation of resources proposed by researchers for a comprehensive, integrated psychological guarantee whose good results have recently been revealed. Key words: psychotherapy, eye movements, positive psychology, optimism protocol, psycho-oncology, resource development and installation, cancer